Exploring the relationship between effective and reflective practice in applied sport psychology - Cropley, B.; Hanton, S.; Miles, A.; Niven, A. G. (The Sport Psychologist, 2010)
This study offers an investigation into the concept of effective practice in applied sport psychology (ASP) with emphasis being placed upon the role that reflective practice may have in helping practitioners to develop the effectiveness of their service delivery. Focus groups (n = 2), consisting of accredited and trainee sport psychologists, were conducted to generate a working definition of effective practice, and discuss the concept of effectiveness development through engagement in reflective practices. The resulting definition encapsulated a multidimensional process involving reflection-on-practice. Initial support for the definition was gained through consensus validation involving accredited sport psychologists (n = 34) who agreed with the notion that although effectiveness is context specific it is related to activities designed to meet client needs. Reflective practice emerged as a vital component in the development of effectiveness, with participants highlighting that reflection is intrinsically linked to service delivery, and a key tool for experiential learning.